Studi Etnografi Dinamika Implementasi Tapping Box dan Simak di Badan Pengelolaan Pajak dan Retribusi Daerah di Lampung Selatan Ethnographic Study of The Dynamics of Implementing Tapping Box and Simak Applications in The Regional Tax and Retribution Mana - Kusumawardhani, Devi; Hanum, Dulatif; Pratama Nugraha, Budi Sutiono (EBBANK, 2024)
This ethnographic study aims to explore the dynamics and cultural practices surrounding the implementation the Tapping Box and  SIMAK applications at the BPPRD Lampung Selatan. Through participant   observation, in depth interviews, and contextual analysis, this research delves into the daily interactions and routines of BPPRD staff and taxpayers. Cultural factors, such as resistance to change and varying levels of technological literacy, play significant roles in the implementation process. The theory indentified are  Innovation Diffusion Theory, Transformational Leadership, and Social System Theory.